2018
DOI: 10.20944/preprints201810.0109.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Petrographic Characteristics and Physico-Mechanical Properties of Aggregates on the Quality of Concrete

Abstract: This paper examines the effect of the aggregate type on concrete strength and more specifically how the petrographic characteristics of various aggregate rocks as well as their physico-mechanical properties influences the durability of C 25/30 strength class concrete. The studied aggregate rocks are derived from Veria-Naousa and Edessa ophiolitic complexes as well as granodiorite and albitite rocks from their surrounding areas in central Macedonia (Greece). Concretes are produced with constant volume proportio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In recent years, many researchers have studied the freeze–thaw resistance of concrete [ 3 , 4 , 5 , 6 , 7 ] and established corresponding freeze–thaw damage models [ 8 , 9 ]. For example, Petros Petrounias [ 3 , 4 ] and Wojciech Piasta et al [ 5 ] studied the effect of coarse aggregate performance on concrete under ordinary temperature and freeze–thaw conditions, respectively, and the results showed that the resistance of the aggregate to freezing and thawing was demonstrated to agree with the values of crushing resistance and the lowest contents of pores with diameters unsafe in terms of the freeze–thaw resistance. Bahram M. Taheri et al [ 6 ] evaluated the freeze–thaw durability of pervious concrete specimens using the JC446-91 test method and revealed that the conditions and number of cycles used in JC446-91 were inadequate to evaluate the freeze–thaw durability of pervious concrete, especially for strong mixes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many researchers have studied the freeze–thaw resistance of concrete [ 3 , 4 , 5 , 6 , 7 ] and established corresponding freeze–thaw damage models [ 8 , 9 ]. For example, Petros Petrounias [ 3 , 4 ] and Wojciech Piasta et al [ 5 ] studied the effect of coarse aggregate performance on concrete under ordinary temperature and freeze–thaw conditions, respectively, and the results showed that the resistance of the aggregate to freezing and thawing was demonstrated to agree with the values of crushing resistance and the lowest contents of pores with diameters unsafe in terms of the freeze–thaw resistance. Bahram M. Taheri et al [ 6 ] evaluated the freeze–thaw durability of pervious concrete specimens using the JC446-91 test method and revealed that the conditions and number of cycles used in JC446-91 were inadequate to evaluate the freeze–thaw durability of pervious concrete, especially for strong mixes.…”
Section: Introductionmentioning
confidence: 99%
“…In concrete paving blocks, the dominant constituent is an aggregate, and as emphasized by Petrounias et al [ 28 ], aggregate has a major impact on a concrete’s properties. However, the goal of the research was to investigate the concrete pavement’s photocatalytic properties.…”
Section: Methodsmentioning
confidence: 99%
“…In some cases, they react with the alkaline pore solution of the concrete. Accordingly, the alkali–silica reaction (ASR) occurs in concrete [ 8 ], which is a deleterious swelling reaction between the highly alkaline pore solution [ 9 ] and the amorphous reactive silica present in some common aggregates [ 10 ], as it draws water from the surroundings. This reaction is a two-step process: (i) alkalis react with the reactive silica present in the aggregate producing alkali-silica gel; (ii) such alkali–silica gel imbibes water and swell producing expansion.…”
Section: Introductionmentioning
confidence: 99%